If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2r + -4t + 3t = 0 Combine like terms: -4t + 3t = -1t 2r + -1t = 0 Solving 2r + -1t = 0 Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add 't' to each side of the equation. 2r + -1t + t = 0 + t Combine like terms: -1t + t = 0 2r + 0 = 0 + t 2r = 0 + t Remove the zero: 2r = t Divide each side by '2'. r = 0.5t Simplifying r = 0.5t
| (a+6)+2bi=6-i | | 0.99n=10+0.89n | | 4w+10=42 | | -5.1s=66.3 | | 15-2b-5=-9 | | 12.54+.12(x+3)=13.04-.14 | | 51=-3x^2-3 | | 10b+4(3b-2)= | | 2n+4+3=1 | | Log243n=4/5 | | 6x+5=-7+3x+18 | | 32z^2=18 | | 3x-[x-(4x+2y)+4y]-5= | | -3x-7=6(x+3) | | n/0 | | 10/8=x/20 | | a^2-a+10=10 | | 8-5x=x+8 | | 7+0.20n=5+0.30n | | ln(x+3)=ln(10)-ln(x) | | (8-4)8x-9y=4 | | 16+5x=4(3x+7) | | 4a-(3a-2b)+3a= | | 5x-45=3x-7 | | 100+80n=250+70n | | 22=x+6+7x | | 8nx=-104 | | 4b-3=3b+5 | | 24=-5-t | | (2x^3-5x^2-3x)-2x^2= | | 8x/5-1/5(2-5x)=38/5+43x/5 | | 14x^-2/(2x)^2 |